2021
DOI: 10.1021/jacs.1c05274
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Enriched α-Borylzinc Reagents by Nickel-Catalyzed Carbozincation of Vinylboronic Esters

Abstract: In this paper is described a synthesis of enantiomerically enriched, configurationally stable organozinc reagents by catalytic enantioselective carbozincation of a vinylboronic ester. This process furnishes enantiomerically enriched α-borylzinc intermediates that are shown to undergo stereospecific reactions, producing enantioenriched secondary boronic ester products. The properties of the intermediate α-borylzinc reagent are probed and the synthetic utility of the products is demonstrated by application to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The use of a bulky and electron-rich diazonium salt was crucial to achieve efficient iodine activation, presumably due to the enhanced stability of the aryl radical. Other notable advances in Cu-catalyzed reactions include the following publications: (1) Cu-catalyzed diazidation reactions; 54 (2) Diastereo-and enantioselective oxidative 1,6conjugate addition; 55 (3) C−H amination of 8-aminoquinoline-directed ferrocenes; 56 (4) Cu-catalyzed hydroxymethylation of alkynes with formic acid; 57 (5) Cu-catalyzed synthesis of indolyl benzo[b]carbazoles; 58 (6) Cu-catalyzed tandem cross-coupling and alkynylogous aldol reaction to access exocyclic α-allenols; 59 (7) Tandem Cu-and Rh-catalysis for oxidation of hydrazones and enantioselective cyclopropanation; 60 (8) Cu-catalyzed CF 2 H-substituted 2-amidofurans; 61 (9) Cu-catalyzed annulation of indolyl α-diazocarbonyl to access carbazoles; 62 (10) Cu-catalyzed enantioselective 1,2reduction of cycloalkenones; 63 (11) Cu-catalyzed enantiodivergent alkynylation of isatins; 64 (12) Cu-catalyzed β-lactam formation from oximes and methyl propiolate; 65 (13) Cucatalyzed aminosulfonylation of O-homoallyl benzimidates; 66 (14) Cu-catalyzed multicomponent trifluoromethylphosphorothiolation of alkenes; 67 (15) Cu-catalyzed chloroarylsulfonylation of styrene derivatives; 68 (16) Cu-catalyzed synthesis of 5-carboxyl-4-perfluoroalkyl triazoles; 69 (17) Crossnucleophile coupling of β-allenyl silanes with tertiary C−H bonds to access 1,3-dienes; 70 (18) Cu-catalyzed C(sp 3 )−H functionalization of O-pentafluorobenzoyl ketone oximes; 71 (19) Total regioselectivity of hydrobromination of alkenes controlled by Fe or Cu catalyst; 72 (20) Enantioselective synthesis of trifluoromethyl cyclopropylboronates by Cu catalysis; 73 (21) Cu-catalyzed asymmetric cyclization of alkenyl diynes; 74 (22) Synergistic Ir/Cu catalysis for asymmetric allylic alkylation of oxindoles; 75…”
Section: Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a bulky and electron-rich diazonium salt was crucial to achieve efficient iodine activation, presumably due to the enhanced stability of the aryl radical. Other notable advances in Cu-catalyzed reactions include the following publications: (1) Cu-catalyzed diazidation reactions; 54 (2) Diastereo-and enantioselective oxidative 1,6conjugate addition; 55 (3) C−H amination of 8-aminoquinoline-directed ferrocenes; 56 (4) Cu-catalyzed hydroxymethylation of alkynes with formic acid; 57 (5) Cu-catalyzed synthesis of indolyl benzo[b]carbazoles; 58 (6) Cu-catalyzed tandem cross-coupling and alkynylogous aldol reaction to access exocyclic α-allenols; 59 (7) Tandem Cu-and Rh-catalysis for oxidation of hydrazones and enantioselective cyclopropanation; 60 (8) Cu-catalyzed CF 2 H-substituted 2-amidofurans; 61 (9) Cu-catalyzed annulation of indolyl α-diazocarbonyl to access carbazoles; 62 (10) Cu-catalyzed enantioselective 1,2reduction of cycloalkenones; 63 (11) Cu-catalyzed enantiodivergent alkynylation of isatins; 64 (12) Cu-catalyzed β-lactam formation from oximes and methyl propiolate; 65 (13) Cucatalyzed aminosulfonylation of O-homoallyl benzimidates; 66 (14) Cu-catalyzed multicomponent trifluoromethylphosphorothiolation of alkenes; 67 (15) Cu-catalyzed chloroarylsulfonylation of styrene derivatives; 68 (16) Cu-catalyzed synthesis of 5-carboxyl-4-perfluoroalkyl triazoles; 69 (17) Crossnucleophile coupling of β-allenyl silanes with tertiary C−H bonds to access 1,3-dienes; 70 (18) Cu-catalyzed C(sp 3 )−H functionalization of O-pentafluorobenzoyl ketone oximes; 71 (19) Total regioselectivity of hydrobromination of alkenes controlled by Fe or Cu catalyst; 72 (20) Enantioselective synthesis of trifluoromethyl cyclopropylboronates by Cu catalysis; 73 (21) Cu-catalyzed asymmetric cyclization of alkenyl diynes; 74 (22) Synergistic Ir/Cu catalysis for asymmetric allylic alkylation of oxindoles; 75…”
Section: Reactionsmentioning
confidence: 99%
“…Inspired by tandem Ni-catalyzed radical addition/crosscoupling chemistry, 9 Morken and co-workers 10 published their recent work on the enantioselective preparation of synthetically versatile α-borylzinc reagents. A large collection of reagents could be accessed via Ni-catalyzed carbozincation of vinyl boronic esters under mild conditions with high enantioselectivity and good yields.…”
mentioning
confidence: 99%
“…These include products bearing sterically hindered arenes (3 b, 3 l), a carboxylic ester (3 j) and heterocycles (3 n, 3 o). Other readily accessible vinylboronates such as the less hindered neopentyl glycol ester variant and the more encumbered methylated acenaphthoquinone derivative [17] were also compatible substrates to afford 3 p and 3 q in good yields and selectivities.…”
mentioning
confidence: 99%
“…These data suggested that the new hydrogen atom of the product originates from silane and also demonstrates the great atom economy of our transformation. Furthermore, using 1-methoxy-4-vinylbenzene (2n) as the starting material to react with 1a, the desired product 4n could not be afforded (3,Scheme 5).…”
mentioning
confidence: 99%
“…Until now, four main kinds of chiral geminated organometallic products have been reported. First, chiral gem-Zr-B, Zn-B, and Sn-B type reagents have been studied by the groups of Srebnik, Morken, and Roush, respectively (A, 1, Figure ). They are useful reagents for making complex chiral molecules, but these reagents worked only for in situ one-pot reaction.…”
mentioning
confidence: 99%